2022
DOI: 10.3390/ani12050546
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Ginger (Zingiber officinale) Residue from Juice Extraction Improves Juvenile Black Rockfish (Sebastes schlegelii) Growth Performance, Antioxidant Enzyme Activity and Resistance to Streptococcus iniae Infection

Abstract: Plant-derived feed additives provide cost effective and environmentally friendly alternatives to antibiotics for improving fish performance in aquaculture. An 8-week feeding trial was conducted to evaluate the effects of dietary ginger residue from juice extraction (GRJE) on juvenile black rockfish (Sebastes schlegelii) growth performance, antioxidant enzyme activities, and resistance to Streptococcus iniae infection. Juvenile rockfish (n = 450; initial weight = 2.2 ± 0.01 g) were randomly distributed into 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
1
2
1
Order By: Relevance
“…The current results agreed with Chung et al (2021), who revealed that the plasma cholesterol level was negatively correlated with elevating levels of the essential oil of ginger in the tilapia niloticus feed. But those findings were dissimilar with that of Oh et al (2022), who reported that the plasma cholesterol levels of juvenile Black Rockfish (S. schlegelii) weren't affected markedly by dietary ginger juice extraction residue supplementation. This decrease was related to the existence of gingerol and shagol compounds in ginger, which inhibit peroxidation of lipid (Ekuagbere et al, 2018).…”
Section: Advances Incontrasting
confidence: 78%
See 1 more Smart Citation
“…The current results agreed with Chung et al (2021), who revealed that the plasma cholesterol level was negatively correlated with elevating levels of the essential oil of ginger in the tilapia niloticus feed. But those findings were dissimilar with that of Oh et al (2022), who reported that the plasma cholesterol levels of juvenile Black Rockfish (S. schlegelii) weren't affected markedly by dietary ginger juice extraction residue supplementation. This decrease was related to the existence of gingerol and shagol compounds in ginger, which inhibit peroxidation of lipid (Ekuagbere et al, 2018).…”
Section: Advances Incontrasting
confidence: 78%
“…Moreover, Naliato et al (2021) demonstrated that dietary ginger powder (2.5, 5, 7.5, 10 and 15 g kg -1 diet) supplementation throughout 30 days improved Oreochromis niloticus growth performance metrics such as final BW, WG, SGR, and FCR. The same results reported in juvenile Black Rockfish (Sebastes schlegelii) (Oh et al, 2022), C. gariepinus juvenile (Iheanacho et al, 2017) fed on different concentrations of ginger powder (0.25%, 0.5%, 0.75%, 1% of diet; 250, 750, and 1000 mg/35 liters of water, respectively). The ginger supplementation at rate of 5 and 10 g kg -1 diet was furthermost suitable for Asian sea bass growth and livability (Talpur et al, 2013).…”
Section: Advances Insupporting
confidence: 71%
“…There were also high significant differences in the content of ALT when feeding Nile tilapia on diets containing ginger at an amount of 12 and 15 g/kg, and there were high significant differences in AST content when feeding Nile tilapia on diets containing ginger at an amount of 9, 12 and 15 g/kg, respectively. While Oh et al (2022) indicated that there were no significant differences in liver enzyme ALT and AST in black rockfish (Sebastes schlegelii) fed on diets to which ginger was added with the control diet.…”
Section: -Alt and Ast: (Alanine Transaminase And Aspartate Transaminase)mentioning
confidence: 97%
“…This plant is also rich in bioactive constituents, such as gingerols, shogaols, paradols, zingerone, terpenes, and zingiberene that play an important role as anti-oxidant, anti-stress, anti-bacterial, anti-fungal, anti-inflammatory, and immunostimulation. [11][12][13][14] The supplementation of ginger extract in aquatic animal's diets has shown positive effects on growth performance in benni fish, Mesopotamichthys sharpeyi, 15 common carp, Cyprinus carpio, 14 black rockfish, Sebastes schlegelii, 16 and Nile tilapia, Oreochromis niloticus. 17 Although ginger is widely researched in fish species, to the best of our knowledge, few studies have reported the effects of its extracts on shrimp as a feed additive.…”
Section: Introductionmentioning
confidence: 99%